Benarkah Cinta Kuat Seperti Maut? Eksegesis Kidung Agung 8:6-7 dan Relevansinya - Jusuf Haries Kelelufna (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2021)
It is really love as strong as death? Exegesis Song of Songs 8:6-7and its relevance. Start from the phenomenon of wealth strength that is able to ' buy love ', the author questioned the truth of the statement 'for love is strong as death' in the book of Song of Songs 8:6-7 which is then analyzed by focusing on the lexicon, context, and syntax of grammar The Hebrew language and compare it to the existing interpretation. The results of the analysis show that Love is something universal included in its erotics love. The nature of Love is described as an extreme force that pushes a person in a positive direction but also negative. Love can build but also tear down. The power of love is confronted with the power of nature and treasures as a challenge as well as proving the power of love. Love with its paradoxical force of extremes can be overcome by the ratification of relationships. The text of the Song of Songs 8:6-7 raises the extreme power of strong love like death, but most of the interpretations are then supported by mystical and materialistic powers to make love ' not ' strong like death  ABSTRAKBenarkah Cinta Kuat seperti Maut? Eksegesis Kidung Agung 8:6-7 dan Relevansinya. Berangkat dari fenomena kekuatan harta yang mampu ‘membeli cinta’, penulis mempertanyakan kebenaran pernyataan ‘karena cinta kuat seperti maut’ dalam kitab Kidung Agung 8:6-7 yang kemudian dianalisis dengan berfokus pada leksikon, konteks, dan sintaks tata bahasa Ibrani serta membandingkannya dengan penafsiran yang telah ada. Hasil analisis menunjukkan bahwa cinta adalah sesuatu yang universal termasuk di dalamnya cinta erotis. Sifat cinta digambarkan sebagai suatu kekuatan ekstrim yang mendorong seseorang ke arah yang positif tetapi juga negatif. Cinta dapat membangun tetapi juga meruntuhkan. Kekuatan cinta diperhadapkan dengan kekuatan alam dan harta sebagai tantangan sekaligus sebagai pembuktian kekuatan cinta. Cinta dengan kekuatan ekstrimnya yang paradoks dapat diatasi dengan pengesahan hubungan. Teks KA 8:6-7 mengemukakan kekuatan ekstrim cinta yang kuat seperti maut, namun sebagian besar penafsiran yang kemudian didukung oleh kekuatan mistis dan materialistik menjadikan cinta ‘tidak’ kuat seperti maut.